Penerapan Model Project Based Learning (PjBL) Berbasis Mind Mapping untuk Meningkatkan Keterampilan Berpikir Kreatif dan Kreativitas Siswa - Annisa Dwi Diningsih; Neng Sholihat; Defrizal Hamka (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2026)
This study aims to determine the application of a mind-mapping Project-Based Learning (PjBL) model to the human digestive system in improving creative thinking skills and creativity in eighth-grade students at SMP Dakwah Pekanbaru. This study used a quantitative approach with a one-group pretest-posttest pre-experimental design. The subjects consisted of eighth-grade students at SMP Dakwah Pekanbaru. The research instruments included a creative thinking skills test, a product creativity assessment sheet, and learning documentation. Data were analyzed using descriptive statistics, the N-gain test, the Wilcoxon test, and the Spearman correlation test. The results showed an increase in students' creative thinking skills after implementing the mind-mapping-based PjBL model, as indicated by an increase in the average posttest score compared to the pretest and a low to moderate N-gain score. Furthermore, students' product creativity was in the good category and had a significant relationship with their creative thinking skills. Thus, implementing the mind-mapping-based PjBL model is effective in improving students' creative thinking skills and creativity in the human digestive system.